ESG Criteria and the Cost of Debt - Kuss, Simon Marius (2021)
This dissertation investigates the relationship between ESG criteria and firms’ cost of debt. It explores three main theories why banks may incorporate ESG considerations into their lending practices and consequently why higher ESG performing companies should benefit from lower borrowing costs. These are a risk reduction effect of ESG, regulatory incentives for banks to lend to high ESG firms and lower information asymmetry. Using a sample of 597 bank loans to firms from 17 European countries covering the years 2010 to 2020, I find that firms which increase their environmental score by one standard deviation benefit from approximately 10 basis points lower loan spreads. This result remains consistent employing an alternative model based on marginal cost of issuing new debt metrics using a larger sample of 3,512 companies. However, results for the impact of overall ESG scores as well as the social and governance dimension on borrowing costs remain inconclusive. Therefore, this study presents strong support in favour of a beneficial relationship between environmental performance and cost of debt implying that banks primarily consider environmental issues in their lending activity and that companies can mainly benefit from lower borrowing costs by focusing on the management of key environmental issues.